2021
DOI: 10.1101/2021.11.01.466827
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Separable mechanisms drive local and global polarity establishment in the C. elegans intestinal epithelium

Abstract: Apico-basolateral polarization is essential for epithelial cells to function as selective barriers and transporters, and to provide mechanical resiliency to organs. Epithelial polarity is established locally, within individual cells to establish distinct apical, junctional, and basolateral domains, and globally, within a tissue where cells coordinately orient their apico-basolateral axes. Using live imaging of endogenously tagged proteins and tissue specific protein depletion in the C. elegans embryonic intest… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 91 publications
(178 reference statements)
2
7
0
Order By: Relevance
“…We note that some non-migratory AFD-1 foci still localized to lateral membranes during this midline enrichment, suggesting that distinct subpopulations of AFD-1 may exist with differing mobilities. By E20, midline-associated AFD-1 began assembling into junctional rings as previously reported (Pickett et al, 2021).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…We note that some non-migratory AFD-1 foci still localized to lateral membranes during this midline enrichment, suggesting that distinct subpopulations of AFD-1 may exist with differing mobilities. By E20, midline-associated AFD-1 began assembling into junctional rings as previously reported (Pickett et al, 2021).…”
Section: Resultssupporting
confidence: 76%
“…We next investigated whether HMR-1 and PAR-3 are required for tissue symmetry breaking, when LPCs migrate and spread along the intestinal midline at E16. We observed HMR-1 localization in PAR-3 gut(-) embryos and PKC-3 in HMR-1 gut(-) embryos because PAR-3 fluorescence was too dim to reliably track and PKC-3 and PAR-3 always colocalize at this stage (Pickett et al, 2021). By E16, PKC-3 and HMR-1 became brighter in HMR-1 gut(-) and PAR-3 gut(-) embryos, respectively, although still localizing as small foci rather than large LPCs.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…At a global scale across a tissue and even across entire organ systems such as a through gut digestive tract, this local polarity must be coordinated into a global apico-basolateral polarity that is consistent across all connected epithelial cells, regardless of their origin or their polarity establishment mechanisms ( Figure 1A ). Recent in vivo work has found that local and global polarity establishment are temporally and genetically separable during the development of the C. elegans intestine ( Pickett et al, 2021 ). In the absence of PAR-3, local pockets of apical proteins align between neighboring cells in a HMR-1/E-cadherin-dependent manner, leading to a cystic, non-functional intestine that lacks global polarity ( Pickett et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vivo work has found that local and global polarity establishment are temporally and genetically separable during the development of the C. elegans intestine ( Pickett et al, 2021 ). In the absence of PAR-3, local pockets of apical proteins align between neighboring cells in a HMR-1/E-cadherin-dependent manner, leading to a cystic, non-functional intestine that lacks global polarity ( Pickett et al, 2021 ). Global coordination of apical membrane initiation sites to one common lumen involves the location of the midbody after oriented cell divisions and cadherin-mediated mechanisms that are independent of cell division ( Jewett and Prekeris, 2018 ; Buckley and St Johnston, 2022 ), as shown in cultured cells ( Schluter et al, 2009 ; Li et al, 2014 ; Lujan et al, 2016 ; Liang et al, 2022 ) and zebrafish development ( Tawk et al, 2007 ; Zigman et al, 2011 ; Rathbun et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%